2006
DOI: 10.1016/j.jneumeth.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Combining laser capture microdissection with quantitative real-time PCR: Effects of tissue manipulation on RNA quality and gene expression

Abstract: Laser capture microdissection (LCM) is increasingly being used in quantitative gene expression studies of the nervous system. The current study aimed at determining the impact of various tissue manipulations on the integrity of extracted RNA in LCM studies. Our data indicate that various tissue preparation strategies prior to microdissection may decrease RNA quality by as much as 25%, thus affecting expression profiles of some genes. To circumvent this problem, we developed a strategy for reverse transcriptase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…To date, few studies using LCM have examined the quality of the isolated RNA; however, a recent study reported that the RNA isolated from LCM of stained cerebellum had an RNA integrity number of Ïł5 (49). Although we had some RNA degradation, this was probably due to staining, which has been shown to decrease RNA quality (49). Since staining is essential for cell localization, some RNA degradation is inevitable.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To date, few studies using LCM have examined the quality of the isolated RNA; however, a recent study reported that the RNA isolated from LCM of stained cerebellum had an RNA integrity number of Ïł5 (49). Although we had some RNA degradation, this was probably due to staining, which has been shown to decrease RNA quality (49). Since staining is essential for cell localization, some RNA degradation is inevitable.…”
Section: Resultsmentioning
confidence: 94%
“…Consequently, the gene profiles that we generated (see below) were reflective of cells in their natural state. We used the RNA integrity number to assess the RNA quality since this has been shown to be the method of choice when evaluating RNA integrity from LCM samples (49). Using the RNA integrity number scale, which ranges from 10 (ideal intact RNA) to 1 (totally degraded RNA (38)), we routinely obtained values Ïł7.5 and Ïł6.6 for limbal and corneal RNAs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sections from these series were also used for mRNA in situ hybridization. The cresyl violet step was omitted to preserve RNA quality (33). Care was taken to ensure that the same level of the dentate gyrus (Bregma = −3.30) was taken from each rat (34).…”
Section: Methodsmentioning
confidence: 99%
“…The 28S/18S rRNA ratio was used to assess RNA quality, using the respective areas under the 28S and the 18S peaks (Kerman et al, 2006).…”
Section: Obtaining Cdnamentioning
confidence: 99%